Retrospective analysis of omega-3 fatty acids and the DASH diet in hyperlipidemia and hypertension management among obese individuals - Yin, Hongtao; Zhou, Yanqing; Zhou, Yingjun; Ren, Lin; Ma, Lixiang (Frontiers in Nutrition, 2025)
BackgroundCardiovascular disease, obesity, high blood pressure, and abnormal lipid profiles are public health issues. Dietary therapies like the DASH diet and omega-3 supplements show cardiometabolic advantages in Western populations. Few Asian cohort studies have examined the effects on obese people with dyslipidemia and hypertension.ObjectiveThe study aims to evaluate the associations of omega-3 supplementation and DASH diet adherence, individually and in combination on lipid profiles, blood pressure, and metabolic outcomes among Chinese obese adults.MethodsThis retrospective analysis examined data from 3,350 obese adults (BMI ≥ 28 kg/m2) with hyperlipidemia and hypertension, recruited at First Hospital of Qinhuangdao City from March 2023 to February 2025. Validated food frequency surveys and structured self-reports examined dietary adherence, while prescriptions and self-reports confirmed omega-3 consumption. LDL-C, HDL-C, triglycerides, total cholesterol, and systolic and diastolic blood pressure were the main results. Weight loss, glycemic control, and lipid/blood pressure targets were secondary outcomes. Multivariable linear, logistic, and mixed-effects regression models were used for statistical analysis.ResultsAmong participants, 42.7% used omega-3 supplements, 35.2% adhered to the DASH diet, and 22.1% followed both interventions. Combined adherence was associated with the greatest improvements: LDL-C reduction (−31.7 mg/dL), HDL-C increase (+5.8 mg/dL), triglyceride reduction (−45.3 mg/dL), and systolic/diastolic BP reduction (−14.7 mmHg, all p < 0.001). Participants with combined adherence were significantly more likely to achieve both lipid and BP targets (68.6%; OR = 3.74, 95% CI: 3.20–4.40) than those with single interventions. Subgroup analyses revealed stronger benefits among older adults, women, individuals with longer obesity duration, and those with diabetes. Time-dependent analyses confirmed sustained improvements over 24 months. Adverse events were generally mild, with overall adherence remaining above 80%.ConclusionCombined omega-3 supplementation and DASH diet adherence was associated with synergistic improvements in lipid and blood pressure control, weight reduction, and glycemic outcomes. These findings support the implementation of integrated dietary and supplement-based strategies for cardiometabolic risk reduction in obese adults, particularly in Asian populations.